Selección y evaluación de concentraciones de extractos naturales con potencial actividad antibacterial antioxidante e inmunoestimulante sobre el camarón litopenaeus vannamei - Agurto Rodríguez, María Gabriela (2011)
The objective of this research is evaluated the efficacy of some natural substances in the aquaculture growth, to highlight the use of organic products. For this reason it was selected a group of plant substances, for their easy access and their good properties reported in some studies. Some Bacteria are responsible for economic loss in mariculture industry. Consequently it was evaluated the antimicrobial activity against (Aeromonas Vibrio harveyi), intestinal flora of crustaceans (Vibrio parahaemolyticus y Vibrio vulnificus) and a clinical bacterium (Pseudomonas aeruginosa). The plant substances evaluated were garlic (Allium sativum), Noni (Morinda citrifolia), Oregano (Oreganum vulgare), Green tea (Camellia sinensis), Bilberry (Vaccinium myrtillus), Astrágalus (Astragalus membranaceus) and Propoleo, using different concentration of each substance. All of these have antibacterial activity, antioxidant activity and inmunostimulant activity in prawns (Litopenaeus vannamei.) The microbiological methodologies used were Determination of Minimum inhibitory concentrations (MICs) for turbidity, obtaining as result zero turbidity for all bacteria and all concentrations of substances. Because the MICs value in Green tea was equal to the minimum bactericidal concentrations (MBCs). The second methodology was the Determination of the Minimum bactericidal concentrations (MBCs). It was observed a bactericidal activity of V. harveyi against all bacteria. Only the substances of the garlic presented a bactericidal activity against V. parahaemolyticus y V. vulnificus. Finally garlic, oregano and Green tea showed some bactericidal activity in contrast to Noni, that has not any bactericidal effect. The inmunostimulant and antioxidant capacity of the plant substances was evaluated in different concentration, with hemocytes and hemocytes extracts of L. vannamei and immunological test of redox reactions were realized to quantify the superoxide (O2-) formation, by the reduction of NBT. In this test was observed that garlic substances presented antioxidant activity in all concentrations, noni substances only in higher concentrations, oregano and green tea only in lower concentrations. Bilberry substances showed an antioxidant activity. Astrágalus substances had an inmunostimulant activity in all concentrations. In conclusion this research has shown that the bioactive compounds of plant extracts could have a positive effect in animals of aquaculture growth.